Kemampuan Membuat Karya Tulis Ilmiah Guru-Guru Sekolah Dasar - Danial Achmad (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study was intended to investigate the influence of sex education and assertion training toward teenagers’ attitude toward pre-marital sex. Pretest-posttest control groups weere employed. Subjects consisted of 32 teenagers who were divided into three groups. The first group consisting of 11 students were given sex education, the second group consisting of 11 students were given assertion training, and the last group, the control or waiting list group, consists of 10 people. Data were analysed using one way analysis of variance and this was supported with individual data analysis. The study found that there was highly significant influence of sex education toward teenagers’ attitude toward pre marital sex; and assertion training did not contribute to teenagers’ attitude toward pre marital sex although score of pre test and post test was different. This led to the conclusion that sex education was more influential than assertion training in influencing teenagers’ attitude toward pre-marital sex.